2001
DOI: 10.3346/jkms.2001.16.4.532
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Amenorrhea Caused by Hydrocephalus Due to Aqueductal Stenosis: Report of Two Cases

Abstract: Amenorrhea is rarely presented as a manifestation of endocrinological disturbances in patients of chronic hydrocephalus. We describe two cases of secondary amenorrhea caused by hydrocephalus due to aqueductal stenosis. Two female patients of age 30 and 20 yr presented with amenorrhea and increasing headache. Magnetic resonance images revealed marked, noncommunicating hydrocephalus without any tumorous lesion. In one patient, emergent extraventricular drainage was necessary because of progressive neurological d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…There have been less than 30 reported cases of amenorrhea deemed secondary to chronic hydrocephalus [2][3][4]. Among these, six presented with secondary amenorrhea and most of these women regained regular menstrual cycles following surgical correction of the hydrocephalus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been less than 30 reported cases of amenorrhea deemed secondary to chronic hydrocephalus [2][3][4]. Among these, six presented with secondary amenorrhea and most of these women regained regular menstrual cycles following surgical correction of the hydrocephalus.…”
Section: Discussionmentioning
confidence: 99%
“…Less than thirty patients with amenorrhea and hydrocephalus have been reported [2][3][4]. We described a rare association of cystic fibrosis, hydrocephalus resulting from Chari-I malformation, and secondary amenorrhea.…”
Section: Introductionmentioning
confidence: 94%
“…Despite this, endocrinological evaluation of patients with head trauma is important for assessment of their progression. Hormone profiles in coma patients due to head trauma were investigated, and decreases in levels of TSH, luteinizing hormone, and follicle-stimulating hormone were shown, with no change in levels of growth hormone or prolactin [11,12]. Matsuura et al [10] reported increased prolactin levels and no change in TSH levels in patients with acute head trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Many hormonal disturbances associated with increased ICP have been investigated in head trauma, but there is no clear consensus on this issue [11,12]. Despite this, endocrinological evaluation of patients with head trauma is important for assessment of their progression.…”
Section: Discussionmentioning
confidence: 99%
“…HCP is not defined as an isolated disease but rather as a clinical status or, specifically, an imbalance between production and absorption of cerebrospinal fluid (CSF) and/or obstruction of the CSF circulation pathway due to ventricular enlargement, which usually causes increased intracranial pressure syndrome. In patients with HCP, the widespread damage occurring in the cellular, anatomical and biochemical structures of the brain is known to affect cognitive function, mental status, visual function, hearing, and metabolic and hormonal status [1,2,3,4]. …”
Section: Introductionmentioning
confidence: 99%